Design optimisation towards lower embodied carbon of prefabricated buildings: Balancing standardisation and customisation - Yiming Xiang; Abdul-Majeed Mahamadu; Laura Florez-Perez; Yanhua Wu (Developments in the Built Environment, 2024)
The design principle of standardisation is widely acknowledged for its potential in reducing embodied carbon emissions (CE) in prefabrications through the facilitated reuse of prefabricated elements. Yet, its effectiveness in optimising CE in precast constructions remains underexplored. This article introduces a micro-level sustainable design optimisation approach for precast projects that factors the CE of both building materials and concrete formwork. Using a parametric approach, the method generates design alternatives derived from the original architecture design. Structure analysis is then employed to determine the design of structure elements and formwork pieces. With the objective of minimising CE from building materials and formwork, a genetic algorithm (GA) is used to explore solutions with the lowest CE. Comparative analysis shows this approach's effectiveness over standardisation-only designs, reducing concrete, reinforcement, precast formwork, and overall CE by 14.32%, 16.71%, 10.39%, and 10.51%, respectively. These findings underscore that increased standardisation does not necessarily lead to lower embodied CE. Integrating the benefits of element standardisation and customisation presents a promising carbon reduction strategy. The introduction of micro-level variables enhances the understanding of standardisation and offers novel carbon reduction strategies, such as increasing the adaptability of casting formwork and maximising the use of existing formwork pieces. Designers and manufactures can adopt these strategies for lower embodied CE of projects. This study also addresses the limitations of design tools used in early architecture design stages, providing designers with continuous decision-making assistance, thereby facilitating the implementation of sustainable strategies.